Rapid One-of-a-kind Product Development Strategies, Algorithms and Tools - Xie, Shane (Shengquan); Tu, Yiliu (Springer London : Imprint: Springer, 2011)
Rapid One-of-a-kind Product Development discusses research in the development of new enabling technologies for small and medium companies. Scientific advancements presented include a novel product data modelling scheme to model product design, manufacturability and knowledge under a common data object; customised product development in a distributed environment; and new adaptive scheduling methods for the optimal production of a wide variety of customised products, taking into consideration all of the possible changes from customers and the uncertainties in manufacturing. The book also includes research towards a computer aided customer interface, which allows customer requirements and changes to be processed and integrated with technical designs in real time; adaptive and concurrent CAD methods and algorithms; and product modelling and system integration technologies. The reader will learn how to: • translate customer requirements to technical attributes; • develop new and innovative products to meet customer requirements and expectations; • evaluate and optimise a project design; • design production systems and use them efficiently; and • manage a variety of customised products. Rapid One-of-a-kind Product Development demonstrates how to develop new methods, tools and algorithms to address the problems in a mass customisation environment. It is a valuable source of information for researchers and engineers in the fields of design and manufacturing.